PEMBUATAN SENYAWA METIL ESTER YANG DITURUNKAN DARI DARI MINYAK BIJI BINTARO (Cerbera manghas L.) SEBAGAI BAHAN BAKU DASAR PEMBUATAN SURFAKTAN - Ilham Burhanuddin; Daniel Daniel; Erwin Erwin (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2019)
Synthesis methyl ester can be formed from kernel bintaro oil (Carberra Mangas L.) with two stages which is esterification and trans-esterification. The test result of methyl ester of bintaro kernel oil have iod value 92,82 g iod/100 gr oil, acid value 1,67 mg KOH/g oil with acid concentration 12,470% and saponification value 185.225 mg KOH/gr oil. From GC-MS analysis fatty acid dominant composition from methyl ester is methyl oleat with walue 45.86%. From HLB analysis show value 0,539. Result of analysis of FT-IR show methyl ester from bintaro kernel oil have typical absorbtion peak on wave number 17443.65 (C=O Ester).